Relationships between Joint Pain, Passive Pain Coping, Sleep Quality and Health – related Quality of Life in Patients with Gout - Oumtanee, Paweena; Jitpanya, Chanokporn (Journal of Health Sciences and Wellness, 2020)
This descriptive research was to investigate health-related quality of life in patients with gout and relationships between joint pain, passive pain coping, sleep quality and health-related quality of the patients’ life. The 143 patients with gout were recruited from patients who follow up at the Department of Rheumatology of Faculty of Medicine Vajira Hospital, Phramongkutklao Hospital and Police General Hospital using a simple random technique. Research instruments consisted of 8 parts: 1) the demographic patients’ data, 2) chronic pain grade questionnaires, 3) the pain coping inventory (PCI), 4) the Pittsburgh sleep quality index (PSQI), 5) the short form health survey-36. Content validity was examined by eight experts and reliability was tested using Cronbach’s alpha coefficient as 0.78, 0.91, 0.80, and 0.88, respectively. Data were analyzed using mean, standard deviation, and Pearson’s product moment correlation. The results of this study revealed that patients with gout had poor level of health-related quality of life (x̄ =338.68, SD= 116.20) and joint pain, passive pain coping, poor sleep quality were negatively significant correlated with health-related quality of life with gout patients at the level of 0.01 (r=-0.490, -0.456, and -0.430, respectively).